Too Much of a Good Thing? Product Proliferation and Organizational Failure - Barnett, William P.; Freeman, John (Organization Science, 2001)
When organizations make important changes, such as introducing products based on new technologies, they may gain strategic advantages but they also experience disruptions. We argue that these disruptions are especially strong when organizations introduce multiple products simultaneously, leading to a temporary increase in the hazard of organizational failure. To test this hypothesis, we study the effects of new product introduction on the survival of U.S. semiconductor manufacturers. We find that having a large number of products—especially innovative products—lowers organizational mortality rates, but that mortality rates increase because of the simultaneous introduction of multiple products. This hazard is substantial, amounting to an increase in the market exit rate of over 40% for the “average” case of simultaneous product innovation. These results are robust in models that control for a wide variety of other factors. Our findings call into question the idea that organizations can overcome disruptions from structural inertia by introducing multiple products simultaneously.